Tingkat Stress Siswa SMA pada Kondisi Pembelajaran Jarak Jauh dimasa Pandemi Covid-19 - Muhammad Rochman; Abd Wahid; Mujib Hannan; Eko Mulyadi (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2022)
Various learning demands must be completed, such as pressure to improve school performance with a sufficient number of grades, various school assignments, UTS, UAS, feeling wrong in choosing majors, and difficulties in managing finances which can cause students' inability to adapt to these conditions. This causes students to experience stress. This study aimed to describe the stress level of high school students in distance learning conditions during the Covid-19 pandemic in Ketapang Daya Village, Ketapang District, Kab. Lacquer. This research is a descriptive study with a population of 76 high school students with a sample of 64 high school students according to the sample criteria using a simple random sampling technique. The results showed that the stress level of high school students during the Covid-19 pandemic showed that most (53.1%) experienced moderate stress, as many as 34 respondents, and a small portion (46.9%) had mild stress, as many as 30 respondents. The dilemma faced by students during the Covid-19 pandemic is in addition to the demands imposed by the online teaching and learning model. The learning process using online media is more tiring and boring because they cannot interact directly with teachers and other students. So that the experience causes frustration for students, and if it continues, it can cause stress.